PREFERENSI Tetrastichus brontispae FERRIERE TERHADAP KUMBANG JANUR KELAPA Brontispa longissima GESTRO DAN PENGARUH KERAPATAN PARASITOID - Zahlul Ikhsan (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2016)
Preferences of Tetrastichus brontispae Ferriere and the influence of population density areimportant to known to determine the propagation techniques are effective and efficient. Theobjective of this research were to study the stage of Brontispa longissima that mostpreference by T. brontispae and ideal comparison between T. brontispae and B. longissimafor propagation. The study consisted of two parts: 1) Preferences of T. brontispae againstlarvae and young pupae of B. longissima. 2) The effect of population density on thedevelopment of parasitoid T. brontispae. Results of the studies showed T. brontispaepreference to young pupae of B. longissima compared with the fourth instar larvae and thirdinstar larvae for parasitization. The average number of young pupa, fourth instar larvae, andthird instar larvae were parasitization row is 4.80 ± 0.52, 2.0 ± 0.47 and 0.6 ± 0.42. Thenumber of adult parasitoids emerged most is the treatment with the one parasitoid female,as many as 17.20 individual. Developmental time from egg to adult each density treatmentrespectively are 17.50; 18.80; 20.80; 22.50 days, and none of adult parasitoid emerged onthe density of 9 tails parasitoid females. Population density of parasitoid T. brontispaesignificantly affect the number of offspring and developmental time from egg to adult.